UJI VISUAL THERMOGRAPHY PADA OSCILLATING HEAT PIPE - Sukadana, Ida Bagus Putu (Jurnal Teknologi Terapan, 2019)
Oscillating Heat Pipes one of the new family of heat pipe is two-phase heat transfer technologies with excellent performance capabilities, simple structure and low production costs. As one of the non-intrusive method in temperature measurement, thermography observation in OHP still very rarely to use although the result was able to explain the relation between temperature oscillation and fluidic motion of fluid. Furthermore this paper aims to study the behavior of thermal profile with the thermography observation. Water with filing ratio (45%) has been chosen as the working fluid for the close loop OHP. The heating power was varying into the evaporator section of OHP from 12 until 142 Watt. It was found that thermography observation very useful tools to define internal flow pattern inside OHP channel. Intermittent oscillation, circulation and dry-out phenomenon was captured more better than conventional temperature measurement. The lowest thermal resistance was found 0.234 °C/W corresponding with 3210 Watt/mK effective thermal conductivity at heat input 142 Watt.